Vagus nerve stimulation inhibits pyroptosis and improves outcome of cerebral ischemic stroke by upregulating osteopontin (SPP1) to disturb ASC oligomerization - Jun Wen; Hao Tang; Ling Wang; Qinghuan Yang; Yong Zhao; Yu Ren; Ting Qin; Xuemei Li; Jianfeng Xu; Gongwei Jia; Qin Yang (BMC Medicine)
Abstract Background Vagus nerve stimulation (VNS) brings new hope for handling stroke. Our previous study confirmed that VNS could reduce neuronal pyroptosis and improve stroke prognosis. However, how VNS suppresses pyroptosis remains poorly understood. Osteopontin (OPN,SPP1) plays a neuroprotective role. Therefore, this study aims to determine whether vagus nerve stimulation (VNS) inhibits pyroptosis and promotes recovery from cerebral ischemic injury through osteopontin (OPN), and to elucidate the mechanisms by which OPN regulates pyroptosis. Methods Acute ischemic stroke (AIS) patients and healthy controls were recruited. The middle cerebral artery ischemia–reperfusion (MCAO/R) model of rats in vivo, the oxygen–glucose deprivation and reperfusion (OGD/R) and lipopolysaccharide (LPS) + adenosine triphosphate (ATP) models of microglia in vitro were established. Gene analysis of GEO public dataset (GSE61616), analysis of proteomics, western blotting, Co-immunoprecipitation (Co-IP) analysis, immunofluorescence staining, ELISA, TTC staining, TUNEL staining, transmission electron microscopy (TEM), scanning electron microscopy (SEM) and neurological function score were used to examinate expressions or concentrations of osteopontin, pyroptosis-related molecules, OPN-ASC interaction, infarct volume, neurological function, cell membrane pore, respectively. Results In MCAO/R rats and AIS patients, osteopontin levels were elevated. Intranasally administered recombinant osteopontin (rOPN) and VNS reduced pyroptosis and improved neurological deficits. VNS upregulated osteopontin expression in MCAO/R rats and AIS patients. Small interfering OPN RNA (siOPN) reversed effects of VNS on pyroptosis and outcome of MCAO/R injury in rats. The binding energy of OPN and ASC was -11.7 kcal/mol. LPS + ATP enhanced OPN-ASC interaction, and rOPN interfered with ASC oligomerization. Conditioned medium of microglia treated with rOPN reversed LPS + ATP-induced neruonal injury. Collectively, OPN may serve as a potential mediator through which VNS inhibits pyroptosis and improves the outcome of ischemic stroke, thereby representing a promising therapeutic target for stroke treatment. Conclusions These findings suggest that VNS alleviates pyroptosis and improves the outcome of cerebral ischemic stroke by upregulating osteopontin (OPN), which interferes with ASC oligomerization. Graphical Abstract